Determinan Kejadian Drop Out Penggunaan Kontrasepsi Pada Pasangan Usia Subur (PUS) Di Kabupaten Kuningan - Siti Nunung Nurjannah; Euis Susanti (Lembaga Penelitian Sekolah Tinggi Ilmu Kesehatan Kuningan, 2017)
Contraceptive use is one of the strategies for population control, but the incontinence of contraceptive use is a problem that is as much as 27 percent of women discontinue use of contraception within 1 year. Higher dropout rates on non-long-term contraceptive methods compared with long-term contraceptive methods. Acceptors who experience Drop Out in Kuningan Regency is 13.74 percent, morer than the target set by 10 percent. The purpose of this research is to find out the determinant related to the incidence of drop out of contraceptive use in the fertile couples in Kuningan District in 2017. The type of this study was observational analytic, using case control design with sample 172 consisting of 86 cases and 86 controls. Case is fertile age couple which has been declared drop out since 1 year after using contraception for 5 years and control that is fertile age couple who still use contraception until done by research. The study was conducted from February to September 2017 with univariate and bivariate analysis with Chi-square statistical test. The result of bivariate analysis of maternal age (p: 0,87, OR: 1,04), parity (p: 0,047, p: 0,049, OR: 6,6, OR: 4,43), education level (p: 0,958 , p: 0.449, p: 0.701, OR: 0.88, OR: 1.64, OR: 1.54), income level (p; 0.988, OR: 1.04),knowledge (p: 1, OR: 1). Contraceptive methods (p: 0.036, p: 0.47), types of IEC (Communication, Information, education) services (p: 0.408, OR: 0.70), contraceptive counseling (0.321 , OR: 1.48) and contraceptive service quality (p: 0.768, OR: 0.86). The conclusions of internal and external determinants related to the incidence of contraceptive users drop out are parity and contraceptive methods in Elderly Couple (EFA). Suggestion, it is expected to local government to increase publicconfidence to all contraceptive methods, in order to be used according to condition and requirement.